A Deformable Motor Driven by Dielectric Elastomer Actuators and Flexible Mechanisms - Minaminosono, Ayato; Shigemune, Hiroki; Okuno, Yuto; Katsumata, Tsubasa; Hosoya, Naoki; Maeda, Shingo (Frontiers in Robotics and AI, 2019)
Soft robots with dynamic motion have a potential to apply for various purpose to treat fragile stuffs. On the other hand, rotational motors potentially are used as one of main actuators to provide functions for robots (such as vibration, locomotion, and suction). A rotational motor which does not prevent the soft robots from deforming is required for providing further applications for the soft robots. In this paper, we developed a deformable motor based on dielectric elastomer actuators (DEAs). The deformable motor has advantages in low-energy consumption, light-weight, and no-generation of magnetic field. We conducted on two experiments. In a visualize experiment, we confirmed that the internal stress from the DEA transmitted to the mechanism for rotating the motor. In a performance experiment, we demonstrated that performance of the deformable motor changed as deforming by external force. We observed the fact that the rotational performance is not likely to decrease when the external force is applied to deform as an elliptical shape. Our developed motor opens up a field for applying the rotational motion to the soft robots.